x=6(2x+1)

Simple and best practice solution for x=6(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=6(2x+1) equation:


Simplifying
x = 6(2x + 1)

Reorder the terms:
x = 6(1 + 2x)
x = (1 * 6 + 2x * 6)
x = (6 + 12x)

Solving
x = 6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
x + -12x = 6 + 12x + -12x

Combine like terms: x + -12x = -11x
-11x = 6 + 12x + -12x

Combine like terms: 12x + -12x = 0
-11x = 6 + 0
-11x = 6

Divide each side by '-11'.
x = -0.5454545455

Simplifying
x = -0.5454545455

See similar equations:

| -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h |

Equations solver categories